NEW ACCOUNTING STANDARD INFORMATION BASED PROSPECTIVE - Choy Zevallos, Elsa Esther (2011)
Today decisions are made on the basis of information present and futureis not enough information in the historical financial statements, prepared and published in relationto what happened inthe past.For economic agents is particularly important information that enables them to analyze and considerthe possibilities of future events that will facethe company. Evidence relating to prospective financial information, but parti allyappliedin piece meal and with out adopting a particular model. This paper presents the following hypothesis"states prostectiva information should be prepared on the basis ofcriteria consistent with prior periods,the accounting rules applying to verify with any degree ofre asonableness the contingencies that will face businesses." The aimis to establish the need for prospective financial information, incorporating accounting for estimates, for displaying future events, sothatwould determine which prospective financial information bylinking information is achievedin the past and the future prospects ofthe company. There search designis descriptive as it seeks to identify, analyze, and evaluate the processes of screening for the prospective financial information.